2004
DOI: 10.1002/bltj.20006
|View full text |Cite
|
Sign up to set email alerts
|

Transport protocol considerations for session initiation protocol networks

Abstract: The session initiation protocol (SIP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Selection of transport layer protocol is effective for the efficiency of SIP signalling. In , different options for the selection of transport layer protocol were qualitatively studied for SIP. In , the effect of applying different transport layer protocols on the delay of establishing call was studied.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Selection of transport layer protocol is effective for the efficiency of SIP signalling. In , different options for the selection of transport layer protocol were qualitatively studied for SIP. In , the effect of applying different transport layer protocols on the delay of establishing call was studied.…”
Section: Related Workmentioning
confidence: 99%
“…Some factors such as different configurations of servers, size of receptor's memory and the used transport protocol are effective for the efficiency of servers under ordinary load and overload conditions . The efficiency will be reduced considerably without an overload mitigation method .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, another important component, which must be considered, is the percentage of sessions missed, which its reduction influence on the Protocol is evident. Generally, with regard to the compatibility in the interoperability, UDP is considered as the standard transmission protocol for SIP, but we should know that the other protocols such as TCP and SCTP are also reliable and applicable [3] (in some cases, the use of connection-oriented protocols are essential, for example, in the circumstances, which the SIP message transmission length is more than MTU [4]). Whereas, according to the standard, all the implementations of SIP must back-up TCP and UDP [5].…”
Section: Related Workmentioning
confidence: 99%
“…Another study also revealed the pros and cons of these protocols with SIP signaling [4]. Transport Layer Security (TLS) was also investigated in addition to the three stated protocols in [5]. Different variants of TCP, namely, Tahoe, Reno and selective acknowledgement (Sack) had been investigated in the context of SIP signaling [6].…”
Section: Introductionmentioning
confidence: 99%